Application of enhanced methods of gravity data analysis for mapping the subsurface structure of the bahira basin in Morocco - Lghoul, Meriem; Abd-Elhamid, Hany F.; Zeleňáková, Martina; Abdelrahman, Kamal; Fnais, Mohammed S.; Sbihi, Karim (Frontiers in Earth Science, 2023)
Gravity-based imaging of the subsurface has increased worldwide recently.Improvements in the processing and analysis of gravity data have allowed us to locate the basement surface, map geologic basins, and define structural patterns. In this study, gravity data were analyzed to study the Bahira basin's underlying geology. The Bahira basin is very important economically. The Ganntour plateau is distinctive due to the importance of the phosphate mining resources. Using gravity data, we mapped the subsurface and determined the underlying structural patterns that affect the study area. In this study, we used several techniques to edge detection including Total horizontal derivative (THDR), first vertical derivative (FVD), tilt derivative (TD), and its horizontal derivative (HD) methods. Accordingly, the geological history of the Bahira basin suggests that the main lineaments/faults trends are NE-SW, NW-SE, ENE-WSW, and WNW-ESE. The 3D Euler deconvolution showed the depth and location of lineaments/faults, and matched edge detection results. The eastern Bahira basin's sedimentary layer is 2-8 km deeper according to the Euler technique. Two-dimensional forward modeling along three profiles in the Bahira basin revealed a horst-graben basement structure. The outcomes of this study improved the subsurface topographical variations of the Bahira Basin. The information collected so far can help future studies in the area.